OPTIMALISASI HAK PEMEGANG SAHAM ATAS KEWENANGAN OJK DALAM PELAKSANAAN AKUISISI LEMBAGA JASA KEUANGAN BANK PADA MASA PANDEMI COVID-19 - Andrea Sukmadilaga; R. Kartikasari; Ema Rahmawati (Faculty of Law, Maranatha Christian University, 2021)
After the issuance of PERPPU Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease 2019 (COVID-19) Pandemic and / or In the Context of Facing Threats That Endanger the National Economy and / or Financial System Stability, OJK can give written orders for the Bank to conduct restructuring, one of which is the Acquisition and is authorized to conduct due diligence on prospective Bank Controlling Shareholders. The method used in writing this article is a normative juridical research with a statutory and conceptual approach. The results of the discussion show that the authority of the OJK in implementing the Acquisition has not taken into account the Shareholders' Rights guaranteed in the Company Law as well as any illegal actions by OJK which resulted in a Forced Acquisition or Hostile Takeover. OJK's discretion regarding the implementation of the Acquisition is not in line with the Freedom of Contract Principle because the Bank has independence in the implementation of the GMS for the corporate agenda, the Bank is also part of a Limited Liability Company that is subject to the Company Law so that the Optimization of Shareholders' Rights needs to be improved.